Dork diaries : 6 holiday heartbreak - Russell, Rachel Renée (London : Simon and Schuster, 2014)
Nikki Maxwell's love life is looking up. Her crush, Brandon, has asked her on an almost-date! Nikki wants to ask Brandon to the upcoming school dance, but he's suddenly acting as if he doesn't like her after all. Will Nikki be able to to pluck up the courage to ask him anyway?
No warning.
Keywords: Maxwell, Nikki (Fictitious character) -- Juvenile fiction; Infatuation -- Juvenile fiction; Friendship -- Juvenile fiction; Middle schools -- Juvenile fiction; Friendship; Infatuation; Middle schools; Fiction; Juvenile works